Corporate failure prediction on firm performance of public listed companies - Liu, Boon Hui (Universiti Malaysia Sarawak, (UNIMAS), 2014)
The purpose of this research is to extent the bankruptcy prediction model to predict financial distress among 45 public listed companies in East Malaysia from period 2008 to 2012 by obtain data through secondary data. Applicability of Altman Z-Score Models was used to identify classification on three main zone which are safe, grey or distress zone. The findings indicated 20 out of 45 companies or 44.44% of listed companies were classified as distress zone, 17 or 37.78% of the companies were known as grey zone while 8 or 17.78% companies was classified as safe zone. On the other hand, the findings show most of the companies was face financial distress when global financial crisis on 2008, result shows companies take few years to recover from financial distress. Oil equipment and services sector was classified as safe zone while construction and materials, industrial metals and mining and real estate investment and services sector were classified as distress zone.